MANAJEMEN BENCANA OLEH PEMERINTAH KOTA MEDAN TERHADAP BENCANA BANJIR DI KECAMATAN MEDAN TUNTUNGAN TAHUN 2020 - Jose Onward Sidabutar; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Abstract Disaster management is needed in the prevention and management of flood disasters that occur in areas prone to flood disasters. In the implementation of disaster management, it takes the role of all parties involved in the implementation of flood disaster management, especially the role of the Government, both the Central Government and Regional/City Governments. The purpose of this study is to determine the disaster management carried out by the City Government for flood disasters and to find out what are the factors that hinder the implementation of disaster management carried out by the City Government. In this study the approach used is a qualitative approach and the type of research used is descriptive. The location of this research was conducted in Medan Tuntungan District and data collection techniques were carried out by interviews and documentation. The results of the study concluded that: First, disaster management carried out by the City Government for flood disasters is explained in three stages, namely pre-disaster is the pre-disaster stage consisting of preparedness including the preparation of disaster-prone maps and training of the Rapid Reaction Team, disaster mitigation includes river crossing activities and outreach regarding disaster. When a disaster occurs, it consists of emergency response including disaster response power and logistics provision. Post-disaster is the stage after the disaster occurs consisting of rehabilitation and reconstruction. Second, the inhibiting factors for the City Government in carrying out disaster management are the limited disaster budget owned by the City Government, low public awareness in protecting the environment to prevent flooding, and limited human resources owned by the City Government in carrying out disaster management. Key Word: Disaster management, City Government, Flood disasters